The Influence of Job Factors on the Employee Satisfaction. A Case Study of Salon in Surabaya - Billy Oliver Sumanto (iBuss Management, 2018)
Service industries always related with employee performance. However, to achieve a great employee performance, the employees must be satisfied with his/her job. Many surveys done by researchers from all parts of the world, conclude that happiness of workers is important especially in the service industry.Therefore, the researcher wants to know whether, the statement of happiness of worker is important in-service industries is relevant for the Indonesian business context. The research question of this research is ‘to what extent job factors influence the employee satisfaction’.This research will use a case study which explores the HR practices of Salon in Surabaya in relation to the work satisfaction of its employees. Hence, research will use qualitative data analysis. The result of this is research are, to some extent job factors influence the employee satisfaction. The researcher also found two more factors affecting employee satisfaction which are; passion of working and job fairness  Keywords:Job factors, Employee Satisfaction